Estrogen-Induced Aurora Kinase-A (AURKA) Gene Expression is Activated by GATA-3 in Estrogen Receptor-Positive Breast Cancer Cells - Jiang, Shoulei (Horm Cancer, 2010)
Aurora-A is a proto-oncogenic mitotic kinase that is frequently overexpressed in human epithelial malignancies including in breast and ovarian cancers. The mechanism of transcriptional upregulation of Aurora-A in human breast cancer is not yet elucidated. We report herein that Aurora-A transcription is positively regulated by GATA-3 in response to estrogen in estrogen receptor α (ERα)-positive cells. Transient expression of aurora-A promoter deletion mutants in luciferase constructs identified a GATA binding sequence motif as a functional regulatory element in ERα-positive breast cancer cells. Electrophoretic mobility shift assay identified the binding of regulatory proteins to the GATA element. Anti-GATA-3 antibody generated a supershifted complex. Recruitment of GATA-3 to the aurora-A promoter was verified by chromatin immunoprecipitation analysis with GATA-3 antibody. Ectopic expression of GATA-3 resulted in elevated expression of Aurora-A in both ERα-positive and negative cells while siRNA-mediated silencing led to downregulation of endogenous Aurora-A in ERα-positive cells. Estrogen treatment of ERα-positive cells induced increased Aurora-A expression with enhanced recruitment of GATA-3 to the aurora-A promoter. Finally, in the ACI rat model of estrogen-induced breast cancer, known to be associated with elevated Aurora-A expression, we observed increased expression of GATA-3 in preinvasive and invasive mammary epithelial cells exposed to prolonged estrogen treatment and in developing breast tumors. These results demonstrate a direct positive role of estrogen in regulating Aurora-A expression through activation of the ERα-GATA-3 signaling cascade and suggest that this pathway may be critical in the origin of estrogen-stimulated sporadic breast cancer.